2007
DOI: 10.1302/0301-620x.89b5.19286
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation of the wounds in open fractures

Abstract: Modern principles for the treatment of open fractures include stabilisation of the bone and management of the soft tissues. Wound debridement and irrigation is thought to be the mainstay in reducing the incidence of infection. Although numerous studies on animals and humans have focused on the type of irrigation performed, little is known of the factors which influence irrigation. This paper evaluates the evidence, particularly with regard to additives and the mode of delivery of irrigation fluid. Normal salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 38 publications
(116 reference statements)
0
84
1
3
Order By: Relevance
“…As previously discussed (54,55), early removal of foreign bodies and organic contaminations (56) accompanied by early irrigation and debridement in the first 24 hours play a crucial role in improving the outcome of open fractures (57,58). Our unpleasant experience throws the light on this fact that if the wound has been primary closed or approximated, wound reassess mentation is important.…”
Section: Infectionmentioning
confidence: 94%
“…As previously discussed (54,55), early removal of foreign bodies and organic contaminations (56) accompanied by early irrigation and debridement in the first 24 hours play a crucial role in improving the outcome of open fractures (57,58). Our unpleasant experience throws the light on this fact that if the wound has been primary closed or approximated, wound reassess mentation is important.…”
Section: Infectionmentioning
confidence: 94%
“…22 Lastly, an extensive literature review by Crowley, investigating the time to debridement, showed that the 6 hour rule needs to be re-evaluated. 23 …”
Section: Trauma-surgery Intervalmentioning
confidence: 99%
“…In contrast the antibiotic group had significantly higher energy injuries and this group also had a longer follow up. Another bias in the study was the lack of a control group with warm Normal Saline which is regarded as the solution of choice in lavage (20). Several studies proved that high pressure lavage significantly reduces the bacterial load, but at the same time is associated with significant bone damage (20).…”
Section: Debridement and Lavagementioning
confidence: 99%
“…Another bias in the study was the lack of a control group with warm Normal Saline which is regarded as the solution of choice in lavage (20). Several studies proved that high pressure lavage significantly reduces the bacterial load, but at the same time is associated with significant bone damage (20). Therefore, low pressure lavage should be used which is safe and effective in reducing the infection rate (21).…”
Section: Debridement and Lavagementioning
confidence: 99%